Manajemen Konflik Pasangan Suami Istri yang Menjalani Pernikahan Jarak Jauh Lintas Negara - Qonita Andini, Annisa; Rahardjo, Turnomo; Ratri Rahmiaji, Lintang (Interaksi Online, 2024)
Long distance marriage is prone to triggering more complex problems if compared to marriages entered into in the same or close geographical conditions or distance. Especially for married couples who are in long distance marriage that crossing the countries, it will certainly be more complicated because it will impact the intensity and quality of communication between the two, considering that there are differences in time zones and the activities that each of they had. Particularly for couples who have just entered the first 0-5 years of marriage, this condition adding risk to the complexity of the conflicts that occur. This research aims to describe in depth how conflict management strategies are carried out by married couples who are in long distance marriage across countries using Conflict Mode Instrument Theory as the main theory, as well as The Interactional View and Relational Dialectics Theory as supporting theories. This research uses a qualitative method with a phenomenological approach and interpretive paradigm, while the data collection technique used is in-depth interviews. The results of this research showed that the conflict management of long-distance married couples is basically the same as that of live-in couples, but there are differences in the conflict escalation which is greater and more complex. In this study, 2 (two) types of responses were found that emerged during the initial conflict, namely silence and efforts to open up. It can also be seen that all couples seek conflict management with collaboration and compromise, although at the beginning of the conflict there was a temporary avoidance attitude by some informants which then made things worse. The challenges that arise in conflict management efforts are caused by 3 (three) main things, namely the difference in time zones, the husband's busy schedule, and technical signal disruptions that affect the intensity and quality of communication between spouses. Limitations in the distribution of affection and biological needs are also a challenge for couples and it is not uncommon for this to trigger conflict. There are 2 (two) effects of the presence of conflict felt by couples, namely being able to introspect themselves and understand each other better. However, these results only apply in this study and are not necessarily the same as the experiences of other couples in general because differences in couples' responses and conflict management are influenced by internal factors (character) and external (time, opportunity, conditions).